Farmers go surfing in Mauritius - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A loan programme of the Development Bank of Mauritius has been in operation since 1999 to help modernise the agricultural sector through ICTs. Loans of MUR 30,000 are provided to farmers at 3% for buying computers, thus enabling producers of modest...